(untitled) (Journal of Economic Research & Business Administration, 2017)
Globalization of world economy and the entry of the Republic Kazakhstan in the international market of the equity, creation of market system of accounting and the reporting and transition to IFRS demanded creation of new elements of market economy – firms on rendering accounting services – outsourcers. Outsourcing allows to lower considerably administrative expenses, that most increasing profit of the organization using ausorsingom accounting accounting and internal audit. Taking into account both the development of information and communication technology and the effects of the current recession on global economy, outsourcing company services has been booming all over the world as it is regarded as a way to meet the strategic goals of cutting costs, improving the satisfaction of the clients’ expectations, and of increasing company efficiency and effectiveness. The paper aims at presenting the current issues of outsourcing accounting professional services and IT support of the company accounting. We have analysed aspects referring to the concept of outsourcing, outsourcing management, and BPO (i.e., Business Process Outsourcing). The advantages, disadvantages, and risks of outsourcing have been pointed out. In addition, the process of outsourcing financial – accounting in support of company accounting have analysed.